Migrating out of a crowded labor market: Evidence from Egypt - Anda David; Joachim Jarreau (IZA Journal of Development and Migration, 2017)
We analyze the determinants of emigration at the individual and household level, using three waves of the Egyptian labor market panel survey (ELMPS) covering the 1998-2012 period. Exploiting the panel structure of the data allows us to reduce the risk of reverse causality and to estimate the effect of migrant networks more accurately than in studies based on cross-sectional data. We confirm, in the Egyptian context, the non-linear relationship between household resources and migration propensity, due to migration costs; a larger network of past emigrants from the same community mitigates this selection on wealth, increasing the propensity to migrate among poorer households. We also show that unemployment and informal employment act as incentives to emigrate, suggesting that the scarcity of quality jobs, in particular on the skilled labor market, is one important driver of emigration flows in Egypt. However, these incentives turn into effective migration only in communities with a sufficiently large network of past migrants.
Keywords: J61; O15; F22; 330; International migration; Networks; Migrant selection; Formality; Egypt